Saddam Hussein’s Trial: The American Hegemony and A Good World Governance Tragedy - Faiz Tajul Millah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
After the destruction of the U.S. World Trade Center on September 11, 2001, America was focusing its international political policy on war on terrorism which was further followed by preemptive action and unilateralism toward countries considered as terrorists. One of them is Iraq. Certainly the policy will obstruct the realization of good world governance under the United Nations Program. Attacking Iraq in 2003 was a real proof of the U.S. hegemony over the world as the Super Power country, especially concerning Saddam Hussein’s judicial process which was held by the Iraqi Special Tribunal which was under the U.S. intervention. Theoretically, the judicial process of Saddam Hussein’s case who was accused of genocide toward Kurdish should be held by the International Criminal Court (ICC) under the United Nations. It was not the competence of the Iraqi Special Tribunal. Saddam Hussein’s trial was invalid and violated the principals of international law. This case would obstruct the enforcement of international law supremacy which is one of the requirements of good world governance. Since international politics is under the U.S. hegemony, the realization of good world governance is in jeopardy.Keywords: Governance, politics, hegemony, and law supremacy